Hubungan Penggunaan Gadget Terhadap Perilaku Sosial Anak - Sari, Putri Indah (IKIP Siliwangi, 2024)
The problem stems from the increasing prevalence of gadgets in children's daily lives, which has raised concerns about their potential impact on their social development. As gadgets become more integrated into the family environment, there is a need to explore whether their use may negatively affect children's ability to interact and develop socially. To achieve this goal, the study adopts a quantitative approach and uses cluster random sampling to select 150 parents whose children are enrolled in five kindergartens (TK) in Natar District. These children are between five and six years old, which is a critical period in their social development. Data collection in this research will be done through a structured questionnaire distributed to the parents. This questionnaire is designed to capture both the frequency of gadget use and various aspects of children's social behavior. The study uses Pearson Product Moment Correlation Analysis to examine the relationship between these two variables. In terms of data analysis, the results show a statistically significant relationship between gadget use and social behavior. With a Pearson correlation coefficient of -0.930 and a significance level (sig. 2-tailed) of 0.000 (which is less than the 0.05 threshold), the results indicate a strong, negative correlation. This suggests that higher levels of gadget use are associated with poorer social behavior in children. In conclusion, the study provides evidence that gadget use in young children has a significant impact on social behavior.